2016
DOI: 10.1111/ajo.12565
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal ultrasound features in fetuses with gastroschisis and its prediction in neonatal outcome

Abstract: Extra-abdominal bowel dilatation is a statistically significant marker of complex gastroschisis and associated morbidity. Its presence in infants who had uncomplicated outcomes, suggests that clinically, its usefulness in antenatal counselling is still debatable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
(15 reference statements)
1
24
0
3
Order By: Relevance
“…Частота супутньої патології кишеч ника становить 16-24,1%, у цих випадках гастрошизис класифікують як комплексний, або ускладнений. Прогноз при ускладненому гастрошизисі гірший, із вищим рівнем леталь ності, подовженим терміном госпіталізації та пізнішим переходом на ентеральне харчу вання [13,18,21].…”
Section: вступunclassified
See 1 more Smart Citation
“…Частота супутньої патології кишеч ника становить 16-24,1%, у цих випадках гастрошизис класифікують як комплексний, або ускладнений. Прогноз при ускладненому гастрошизисі гірший, із вищим рівнем леталь ності, подовженим терміном госпіталізації та пізнішим переходом на ентеральне харчу вання [13,18,21].…”
Section: вступunclassified
“…Характерними ускладненнями при гастро шизисі є зміна кількості навколоплодових вод (маловоддя та багатоводдя), затримка росту плода, дистрес та антенатальна загибель, тому рекомендують інтенсивніше антенатальне спостереження [1,13,16,21].…”
Section: вступunclassified
“…Gastroschisis is an AWD characterized by the herniation of the abdominal viscera represented by bowel loops and occasionally parts of other abdominal organs outside the abdominal wall with no covering membrane or sac, to the right of the insertion of the umbilical cord, and rarely to the left side [25,26]. Even if the condition is not generally associated with other major congenital or chromosomal anomalies, an accurate fetal anatomy assessment is required.…”
Section: Gastroschisismentioning
confidence: 99%
“…The incidence of gastroschisis is reported to be 2–5 per 10 000 births. There have been several reports on ultrasound findings, such as bowel dilatation, associated with the postnatal outcome in fetuses with gastroschisis . Although neonatal prognosis is generally good, intrauterine fetal death (IUFD) and nonreassuring fetal status (NRFS) sometimes occur.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on ultrasound findings, such as bowel dilatation, associated with the postnatal outcome in fetuses with gastroschisis. [1][2][3] Although neonatal prognosis is generally good, intrauterine fetal death (IUFD) and nonreassuring fetal status (NRFS) sometimes occur. South et al 4 reported that waiting until 37 weeks' gestation for delivery increased the risk of IUFD in fetuses with gastroschisis.…”
Section: Introductionmentioning
confidence: 99%